The Effect of Financial Performance on Audit Delay with Firm Size as Moderation - Wafi, Muhammad Ismail Hibatul; Wuryaningsih, Wuryaningsih; Nisa, Risya Khaerun (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: This study examines the effect of profitability, solvency, and liquidity on audit delay, with Firm size as a moderating variable. The healthcare sector was chosen due to its strict regulations, service stability, and reporting complexity exacerbated by the impact of the COVID-19 pandemic, making it relevant to study. Method: Research using logistic regression analysis with the assistance of EViews 12 in healthcare sector companies using purposive sampling method. Results: The research results indicate that the variables of profitability and solvency have an impact on audit delay, whereas the liquidity variable does not affect audit delay. Regarding the firm size variable, it can moderate the influence of profitability and liquidity on audit delay, while the firm size cannot moderate the impact of solvency on audit delay. Implications: These results emphasize the importance of transparency and financial management in reducing audit delays in the healthcare sector. The findings are helpful for auditors and regulators in improving audit efficiency and timeliness of financial reporting. Novelty: This research focused on the healthcare sector in Indonesia, which is an innovation from the study conducted by Anggraini et al. (2024). The study employed Return on Equity (ROE) measurement to identify profitability variables.